Near-infrared luminescence of rare earth ions in oxyfluoride lead borate glasses and transparent glass-ceramic materials - Pisarska, Joanna; Ryba-Romanowski, Witold; Dominiak-Dzik, Grażyna; Goryczka, Tomasz; Pisarski, Wojciech A. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Oxyfluoride lead borate glasses singly doped with Nd3+ and Er3+ ions have been studied before and after thermal treatment. The orthorhombic PbF2 crystallites are formed during thermal treatment, which was evidenced by X-ray diffraction analysis. Near-infrared luminescence spectra at 1.06 μm and 1.53 μm have been registered for samples before and after annealing, which correspond to the main 4F3/2–4I11/2 and 4I13/2–4I15/2 laser transitions of Nd3+ and Er3+ ions, respectively. Luminescence decays from 4F3/2 state of Nd3+ and 4I13/2 state of Er3+ have been analyzed in detail. Contrary to Nd-doped samples, the luminescence lines obtained for Er-doped transparent oxyfluoride glass-ceramics are more intense and narrowed, whereas the luminescence decays from 4I13/2 state of Er3+ are slightly longer in comparison to precursor glasses.
Optica Applicata, Vol. 38, 2008, nr 1, s. 211-216
Keywords: optyka; oxyfluoride glasses; transparent glass-ceramics; rare earth ions; luminescence